An exploratory study to evaluate Prime Bank Limited’s online banking service and finding out the outcomes due to centralized IT operation system in banking sector - Afrin, Sadia (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.